Hubungan Riwayat Pemberian Imunisasi Dasar dengan Status Pertumbuhan Bayi Usia 09–24 Bulan di PMB Wiwik Indriani Sungai Ulin - Sundari, Neng; Ilmiah, Widia Shofa (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Child growth is a key indicator of health and well-being in early life. One of the influencing factors is the history of basic immunization. Basic immunization serves as a preventive measure against infectious diseases that may interfere with a child’s physical development. This study aimed to determine the relationship between basic immunization history and the growth status of infants aged 9–24 months at PMB Wiwik Indriani, Sungai Ulin. The study used a descriptive-analytic design with a cross-sectional approach and involved 35 infants selected through total sampling. Data were obtained from immunization records and anthropometric measurements, including weight, height, and upper arm circumference. Analysis using the Spearman Rank correlation test showed a strong positive relationship between immunization history and infant growth status (r = 0.615; p = 0.000). Infants who had completed basic immunization tended to show better growth outcomes. These findings support the importance of complete immunization as a promotive strategy to enhance optimal growth in early childhood.